Controlled ∗-G-Frames and ∗-G-Multipliers in Hilbert Pro-C∗-Modules - Zahra Ahmadi Moosavi; Akbar Nazari (International Journal of Analysis and Applications, 2019)
A generalization of multiplier, controlled g-frames and g-Bessel sequences to ∗-g-frames and ∗-g-Bessel sequences in Hilbert pro-C∗-modules is presented. It is demonstrated that controlled ∗-g-frames are equivalent to ∗-g-frames in Hilbert pro-C∗-modules.